Analysis of the Implementation of Character Education in English Teaching Learning at SMAN 3 Bengkulu Utara - Ferdy Oktavian; Washlurachim Safitri (Teaching English and Language Learning English Journal, 2022)
This descriptive research was aimed to describe how the Character Education implemented by English teachers at SMAN 3 Bengkulu Utara and to find out how the teacher solve the problems during the implementation. The subjects of the research were three English teachers who teach EFL classroom at SMAN 3 Bengkulu Utara. The researcher used observation checklist to obtain the data. There were two findings of this research; (1) There were five aspects of character education implemented by English teachers in teaching English at SMAN 3 Bengkulu Utara namely; religious, nationalism, integrity, independent, and mutual cooperation. However, there were two aspects which were not implemented by all teacher, they were religious and mutual cooperation with percentage less than one hundred percent. (2) There were three ways to solve the problems during the implementation; trying to implement the character education in many chances not only in the classroom but also out of the class, asking the students’ parents to participate in the implementation of character education while the students at home, and asking the students to always become a good person wherever they go and keep in mind that “something good brings goodness”. Keywords : Character Education, English Teaching Learning